Comparative Study on Fire Resistance of Different Thermal Insulation Materials for Electric Vehicle Tunnel Fire - Xiaojun Li; Yuanwei Cheng (Applied Sciences)
With the growing prevalence of lithium battery electric vehicles, the incidence of fires resulting from thermal runaway in lithium batteries is also on the rise. In contrast to conventional fuel vehicle fires, fires involving lithium battery electric vehicles exhibit distinct differences in fire dynamics, fire loads, and smoke characteristics. These variations impose more stringent requirements on the design of passive fire protection systems within tunnels. To evaluate the fire resistance performance of existing passive fire protection systems under electric vehicle fire conditions, this study first used PyroSim software 2022 (integrating FDS 6.7.9) to establish fire models for combustion engine trucks and electric trucks, comparing the combustion characteristics of both types of fires without insulation lining materials. Based on the electric truck fire model, different insulation lining materials were added. The analysis of the simulation results focused on the impact of the thermal conductivity and emissivity of each lining material on peak tunnel temperatures, aiming to identify the insulation lining material with the best fire resistance performance. The results indicate that the heat release rate, temperature distribution, toxic gas concentration, and smoke propagation of lithium battery combustion engine truck fires are all higher than those of combustion engine truck fires. Among the five insulation lining materials studied, SiO2 gel material demonstrated superior fire resistance compared to the others. This research provides a scientific and rational basis for tunnel fire protection design and fire response strategies, aiming to mitigate the damage caused by lithium battery electric vehicle fires to tunnel lining structures.